PENDAYAGUNAAN PEMAHAMAN HAK CIPTA ATAS KARYA LOKAL PENYANDANG DISABILITAS DALAM PENINGKATAN EKONOMI KREATIF - Dirkareshza, Rianda; Desthabu, Meurina; Karunia, Aura Dwi; Bagaskara, Muhammda Fadhil (Jurnal Kreatif : Karya Pengabdian untuk Masyarakat Aktif dan Inovatif, 2024)
There are a number of challenges to work produced by people with disabilities, for example in the context of copyright, it becomes the main focus in community service activities for help people with disabilities register copyright as evidence stronger in terms of legal certainty and product protection being targeted avoid a legal vacuum if it is hampered by a conflict. Together through the Wisma Cheshire Foundation as a forum for empowering and giving greater opportunities for groups of people with disabilities, service activities This community seeks understanding in the utilization of implementation the usefulness of copyright for the works they have produced is expected. One way to increase the value of creative economic growth is by realizing. The dream of disabled friends is to have an MSME. In general, there is one connection between the creative economy and copyright because the development of the creative economy is focused towards the creation of goods or services that rely on talent and creativity can later produce economic benefits to the creator. Methods used in community service this is Participatory Action Research (PAR), PAR is methods oriented towards community empowerment, development and mobilization knowledge. The solutions that will be implemented by the service team include: first, provide education for people with disabilities regarding registration, benefits and others so on regarding copyright as well; secondly, providing facilities in the form of registration assistance copyright for the work they create; third, provide valuable opportunities economically to people with disabilities for the work they create through registration of individual legal entities/Micro, Small and Medium Enterprises is based on economics creative. Disability; Copyright; and Economy Creative